Anemia and pregnancy outcomes in teenage prenatal care clinic at Siriraj hospital - Supapen Lertvutivivat; Pattarawalai Talungchit (The Royal Thai College of Obstetricians and Gynaecologists, 2016)
Objectives: To compare the prevalence of anemia and pregnancy outcomes between teenage pregnancies who received teenage prenatal care services and general prenatal care services at Siriraj Hospital and to evaluate various factors associated with anemia before delivery.Materials and Methods:Medical records of 343 and 347 teenage pregnancies who received antenatal care (ANC) at teenage prenatal care clinic and general ANC clinic for more than 4 times and delivered at Siriraj Hospital were reviewed. Prevalence of anemia at first ANC and before delivery as well as pregnancy outcomes were compared. Various factors associated with anemia were also evaluated.Results:Women in teenage prenatal care clinic were younger (16.9±1.2 vs. 17.5±1.3 years, p<0.001) than women in general prenatal care clinic. Prevalence of anemia at first ANC and before delivery were comparable between 2 groups (26.5% vs. 25.9%, p=0.859 and 20.4% vs. 19.9%, p=0.864). Improvement and deterioration of anemia status were also comparable (57.1% vs. 60.0%, p=0.695 and 12.3% vs. 12.8%, p=0.855). No differences of various pregnancy outcomes were observed including, preterm birth, low birth weight, primary cesarean delivery rates. Logistic regression analysis demonstrates that anemia at 1st ANC and maternal age <17 years significantly increased the risk of anemia before delivery (adjusted OR 4.7, 95% CI 3.1-7.0, and 1.8, 95% CI 1.2-2.8, respectively).Conclusion: No difference of prevalence of anemia and pregnancy outcomes between women attending teenage and general prenatal care clinic. Anemia at 1st ANC and age <17 years old were independent factors for anemia before delivery.